INCREASING MANAGERIAL CAPACITY AND DIGITAL LITERACY THROUGH TRAINING AND MENTORING FOR MSMES IN PILANGREJO DEMAK VILLAGE - Sari, Inayah Adi; Puspitasari, Ratih Hesty Utami; Ilham, Ratih Milati; Yulianti, Fitri (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
The people of Pilangrejo Village, Wonosalam District, most of the people have a livelihood producing smoked fish. Smoked Fish is one of the production alternatives that are in demand by the market because of its taste which tends to be more savory and durable. The problem in the field of production faced by partners is that the smoking process is still traditional, so that the appearance and cleanliness of smoked fish are not well maintained. In addition, it can cause environmental pollution around the production area.The problem in the field of marketing is that the process of selling smoked fish is still carried out conventionally. Partners are not familiar with online product marketing. The solution offered to partners is by training on smoked fish packaging and online sales processes, so that smoked fish can be widely known to the public. As for financial management problems, partners do not understand how to manage personal and business finances. The solution offered is family financial management training, which will later have an impact on business finances. This PKM activity was attended by 60 members of the fish smokers association. The results of this PKM activity make partners able to produce smoked fish cleanly and healthily, partners can also carry out the sales process online, and partners can manage family and business finances well.